Pregnancy Induced Musculoskeletal Problems - Saime Ay (Archives of Rheumatology, 2008)
Many physiological changes occur in the body of the pregnant women. One of them is the changes of the musculoskeletal system. During pregnacy because of the increase in size and weight of the gravid uterus, postural changes that cause functional changes occur in the related muscles.Pre-existing musculoskeletal dysfunctions may be aggravated and new problems may be created by these changes. The earlier musculoskeletal system disorder diagnosis in pregnancy, the better the chance of succesful management of the condition. (Rheumatism 2008; 23: 56-9)